Palladium-catalysed ligand-free reductive Heck cycloisomerisation of 1,6-en-α-chloro-enamides - Hou, Y; Ma, J; Yang, H; Anderson, E; Whiting, A; Wu, N (Royal Society of Chemistry, 2019)
The first example of an intramolecular hydroarylation of 1,6-en-α-chloro-enamides was achieved by a palladium-catalysed ligand-free reductive Heck cycloisomerisation with no competing Heck-cyclised by-product.